Performance Evaluation of OSPF and EIGRP Routing Protocols for Scalable Distributed Network Environments - Akbar Maulana Mubarak; Atep Aulia Rahman (Brilliance: Research of Artificial Intelligence, 2026)
Distributed computer networks require routing protocols capable of maintaining efficient communication as network size and complexity continue to increase. Selecting an appropriate routing protocol is essential to ensure reliable data transmission, efficient routing performance, and network scalability in distributed computing environments. This study compares the performance of two dynamic routing protocols, namely Open Shortest Path First (OSPF) and Enhanced Interior Gateway Routing Protocol (EIGRP), using equivalent distributed network topologies to ensure consistent testing conditions and objective performance evaluation. The experiments were conducted using Graphical Network Simulator 3 (GNS3) for the OSPF implementation on MikroTik RouterOS and Cisco Packet Tracer for the EIGRP implementation on Cisco devices. Network performance was evaluated based on four parameters: latency, packet loss, convergence time, and scalability. The experimental evaluation demonstrated that OSPF achieved lower average latency and established a greater number of neighbor relationships, indicating better scalability and efficient route management within the simulated distributed network environment. In comparison, EIGRP produced lower packet loss while maintaining reliable routing communication throughout the experiments, reflecting its capability to provide stable packet delivery. The convergence performance of both routing protocols was evaluated under the implemented testing scenario, where both protocols demonstrated comparable routing recovery behavior. These findings indicate that each routing protocol offers different advantages depending on network size, topology characteristics, and operational requirements. Therefore, selecting an appropriate routing protocol should consider the expected scalability, communication reliability, and overall performance requirements of the target distributed network environment.